THE INFLUENCE OF THE IMPLEMENTATION OF PERFORMANCE-BASED BUDGET, INTERNAL GOVERNMENT CONTROL SYSTEM ON REGIONAL GOVERNMENT PERFORMANCE WITH ACCOUNTABILITY AS A MODERATING VARIABLE IN DELI SERDANG DISTRICT GOVERNMENT AGENCIES - Widhayanti; Irfan; Dahrani (SEAN Institute, 2023)
The purpose of this study is to analyze the effect of performance-based budgeting and local government internal control system practices in addressing government performance in the OPD of Deli Serdang district and to determine and analyze the impact of accountability to moderate the connection between performance-based budgeting and internal control. This research method uses quantitative methods. The population used in this study was program and planning staff personnel from the Deli Serdang Regency government. The analytical method used was structural equation modeling. The results of this study demonstrate that performance-based budgeting and internal control practices influence government performance and acountability can moderate the connection between performance-based budgeting and internal control. The results of this discovery are expected to provide insight and knowledge about the factors affecting local government performance. Furthermore, this study is expected to provide additional input and relevant evaluation material. Deli Serdang Regency Government Performance Evaluation and Future Guidelines.